Algoritma Blowfish Pada Watermarking Video Digital - Mufida Khairani; Nurwulan Nurwulan (JURIKOM (Jurnal Riset Komputer), 2018)
The use of digital formats, especially in video, voice or music data, is still causing controversy surrounding the protection of copyright. These problems cause the importance of proof of ownership of the copyright of a digital media. To be able to prove ownership of copyright, watermarking techniques can be used. In this study, the blowfish algorithm method is used for digital video watermarking using the VB.Net application. This study aims to protect the copyright of digital video owners by applying the blowfish algorithm so as to increase the watermarking robustness that exists in the digital video. The results of this study are application programs that can be used by all parties. Because this application is very user-friendly.